Assessment of the effects of the carbamazepine on the endogenous endocrine system of Daphnia magna - Oropesa, A. L. (2017)
In the present study, the endocrine activity of the antiepileptic pharmaceutical carbamazepine (CBZ) in the crustacean Daphnia magna was assessed. To assess the hormonal activity of the drug, we exposed maternal daphnids and embryos to environmental relevant concentrations of CBZ (ranging from 10 to 200 mu g/L) and to mixtures of CBZ with fenoxycarb (FEN; 1 mu g/L). Chronic exposure to CBZ significantly decreased the reproductive output and the number of molts of D. magna at 200 mu g/L. This compound induced the production of male offspring (12 +/- 1.7 %), in a non-concentration-dependent manner, acting as a weak juvenile hormone analog. Results showed that this substance, at tested concentrations, did not antagonize the juvenoid action of FEN. Further, CBZ has shown to be toxic to daphnid embryos through maternal exposure interfering with their normal gastrulation and organogenesis stages but not producing direct embryo toxicity. These findings suggest that CBZ could act as an endocrine disruptor in D. magna as it decreases the reproductive output, interferes with sex determination, and causes development abnormality in offspring. Therefore, CBZ could directly affect the population sustainability.